Congenital Heart Disease in East Africa - Jivanji, Salim G. M.; Lubega, Sulaiman; Reel, Bhupi; Qureshi, Shakeel A. (Frontiers in Pediatrics, 2019)
Congenital Heart Disease (CHD) is a huge problem in Low Middle Income Countries and particularly sub-Saharan Africa. There is an estimated 500,000 children born in Africa with CHD each year with the vast majority in sub-Saharan Africa. More than 90% of these children receive sub-optimal or no care at all. In East Africa – Kenya, Tanzania and Uganda have attempted to create a CHD service for the last 20 years with slow growth due to various factors. Visiting cardiac missions have made significant contributions in the developments however there remains a significant number of children with lack of care. We explore the positive aspects of the current projects, the various factors that hinder growth in this area, and what can be done to promote CHD service growth in these countries.